2002
DOI: 10.1177/154193120204601703
|View full text |Cite
|
Sign up to set email alerts
|

Target Acquisition with UAVS: Vigilance Displays and Advanced Cueing Interfaces

Abstract: Future Uninhabited Aerial Vehicles (UAVs) will require operators to switch quickly and efficiently from supervisory to manual control. Utilizing a vigilance task in which threat detections (critical signals) led observers to perform a subsequent manual target acquisition task, the present investigation revealed that the type of vigilance display might have important design implications for future UAV systems. A sensory display format resulted in more threat detections, fewer false alarms, and faster target acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 5 publications
1
17
1
Order By: Relevance
“…For example, voice commands have shown reduced operation time in discrete robotic tasks, but perform poorly for continuous tasks (Redden, Carstens, Pettitt, 2010). Additionally, auditory cues were shown to increase performance within robotic tasks when used alone and in conjunction with tactile cues (Gunn, Warm, Nelson, Bolia, Schumsky, Corcoran, 2005;Haas, 2007). Arm and hand gestures are a natural and intuitive method of communication between humans (Wexelblat, 1995) and can be quicker and feel more intuitive than manual controls (Guo & Sharlin 2008).…”
Section: Operational Definitionsmentioning
confidence: 99%
“…For example, voice commands have shown reduced operation time in discrete robotic tasks, but perform poorly for continuous tasks (Redden, Carstens, Pettitt, 2010). Additionally, auditory cues were shown to increase performance within robotic tasks when used alone and in conjunction with tactile cues (Gunn, Warm, Nelson, Bolia, Schumsky, Corcoran, 2005;Haas, 2007). Arm and hand gestures are a natural and intuitive method of communication between humans (Wexelblat, 1995) and can be quicker and feel more intuitive than manual controls (Guo & Sharlin 2008).…”
Section: Operational Definitionsmentioning
confidence: 99%
“…A recent study by Gunn et al (2005) examined the workload of sustained attention in a situation involving the control of an unmanned aerial vehicle (UAV) in which the vigilance signal warned observers of the presence of an enemy aircraft in the UAV's airspace. Upon detecting that signal, observers (Os) were required to make a manual detection response and then visually search the surrounding airspace to locate and destroy the enemy aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…(1) the chance that the search task was less demanding than the vigilance task and that Os averaged the two in assessing the workload they experienced, a mode of responding that would lower the overall workload score; (2) the beneficial effect of scene appeal, since the search component in the Gunn et al (2005) study required Os to be exposed to natural ground-to-air scenes that were more variegated and interesting than those of traditional vigilance studies; (3) the beneficial effect of knowledge of results (KR) about the accuracy of signal detections inherent in the conditions of the Gunn et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence to date indicates that when observers are allowed some measure of perceived or real control over the task environment, performance is enhanced. Thus, Gunn et al (2005) reported that when observers in a simulated UAV task were permitted to take action against targets they detected, their performance improved and stress symptoms decreased. Further, even the illusion of control can facilitate performance.…”
Section: Introductionmentioning
confidence: 99%